2006
DOI: 10.1111/j.1540-8167.2006.00680.x
|View full text |Cite
|
Sign up to set email alerts
|

Obesity As a Risk Factor for Sustained Ventricular Tachyarrhythmias in MADIT II Patients

Abstract: Our findings suggest that in nondiabetic patients with ischemic left ventricular dysfunction, a BMI > or =30 kg/m(2) is an independent risk factor for ventricular tachyarrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
64
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(69 citation statements)
references
References 21 publications
3
64
1
1
Order By: Relevance
“…After control measurements, obesity hypertension was produced by feeding a high-fat diet for 28 days before reducing fat intake to maintain body weight for the remainder of the study. The experimental protocol consisted of 1) control, days 1-3; 2) days 4 -31, high fat (development of obesity and hypertension); 3) days 32-63, reduced fat (established obesity hypertension); 4) days [35][36][37][38][39][40][41], baroreflex activation (1 wk); 5) days [42][43][44][45][46][47][48], recovery (1 wk); 6) day 49, surgical bilateral renal denervation by procedures previously used in our laboratory (33); and 7) day 63, end of study (2 wk after renal denervation).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After control measurements, obesity hypertension was produced by feeding a high-fat diet for 28 days before reducing fat intake to maintain body weight for the remainder of the study. The experimental protocol consisted of 1) control, days 1-3; 2) days 4 -31, high fat (development of obesity and hypertension); 3) days 32-63, reduced fat (established obesity hypertension); 4) days [35][36][37][38][39][40][41], baroreflex activation (1 wk); 5) days [42][43][44][45][46][47][48], recovery (1 wk); 6) day 49, surgical bilateral renal denervation by procedures previously used in our laboratory (33); and 7) day 63, end of study (2 wk after renal denervation).…”
Section: Methodsmentioning
confidence: 99%
“…obesity; hypertension; heart rate variability; baroreflex; sympathetic nervous system THE CAUSAL LINK between obesity and hypertension is well recognized. Clinical and experimental evidence also indicate that obesity has a profound impact on cardiac automaticity (44), which may increase the risk for atrial and ventricular arrhythmias, leading causes of morbidity and mortality in the industrialized world (4,7,17,42,59,60). The mechanisms that mediate the proarrhythmogenic effects of obesity have received little attention.…”
mentioning
confidence: 99%
“…20 Sudden death could be related to arrhythmic events, including lethal ventricular fibrillation, because patients with MetS had significantly higher values of corrected QT interval and QT dispersion on ECG, which reflects myocardial refractoriness and electrical instability. 21 In the Multicenter Automatic Defibrillator Implantation Trial II (MADIT-II) study, 22 obesity (BMI ≥30 kg/m 2 ) was a risk factor for sustained ventricular tachyarrhythmia in patients after myocardial infarction with severe LV dysfunction (LV ejection fraction <30%).…”
Section: Sudden Death and Arrhythmiamentioning
confidence: 99%
“…16 In an attempt to identify those criteria, post hoc analyses of the second Multicenter Automatic Defibrillator Implantation Trial (MADIT II) revealed several clinical criteria associated with an increased risk for ventricular arrhythmias resulting in appropriate device therapy. [17][18][19] Thus far, however, in patients with low LVEF, no criteria have been recognized that may identify patients at low risk of ventricular arrhythmias during follow-up. If possible to identify a low-risk population, ICD therapy in this group may be reconsidered.…”
mentioning
confidence: 99%